Biodegradable plastics from linier low-density polyethylene and polysaccharide: The influence of polysaccharide and acetic acid - Dwi Wahini Nurhajati; Bidhari Pidhatika; Syaiful Harjanto (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2019)
Global problems associated with conventional, non-biodegradable plastics have urged the society to use more eco-friendly biodegradable plastics. In this study, linear low-density polyethylene (LLDPE) was co-compounded with cassava-based thermoplastic starch (TPS) to prepare biodegradable plastics (i.e. plastics that can be degraded by microbes), in which three different LLDPE/TPS ratios were studied. Acetic acid was used to hydrolyze the polysaccharides by breaking the branched amylopectin that causes the TPS-containing composites brittle and stiff. The biodegradation properties of the LLDPE/TPS composites were determined by observing the level of microbial growth on the sample surface after incubation with potato dextrose agar medium that was inoculated with Penicillium sp. and Aspergillus niger. Burial test in a humid composting medium was also performed to validate the biodegradation properties. The mass change (%) was calculated in relative to the initial mass before burial test. The physical properties (tensile strength and elongation at break) of the bioplastics were determined using universal testing machine before and after burial treatment. The morphology of the sample surface was evaluated using scanning electron microscopy. The results showed that the microbial growth increases with increasing TPS content. Negative mass changes were observed on all samples that contain TPS, with increase in the magnitude with increasing TPS content. The tensile strength tends to increase in the first 28 days of burial period in a composting medium then decreases and plateaus, while the elongation at break decreases with increasing burial period. Moreover, samples that contain acetic acid showed less microbial attachment and less biodegradation compared to samples that does not contain acetic acid.